Subcritical crack growth behavior and life data analysis of two types of dental Y-TZP ceramics - Mitov, Gergo; Gessner, Janina; Lohbauer, Ulrich; Woll, Karsten; Muecklich, Frank; Pospiech, Peter (Dental Materials, 2011)
Objectives: The aim of this study was to evaluate the mechanical properties and the subcritical crack growth behavior of a presintered dental Y-TZP (Kavo Everest ZS) and a hot isostatic pressed Y-TZP (Kavo Everest ZH) and to perform life data analysis. Methods: For each material 150 bending bars were produced. The initial fracture strength was determined in a four-point bending test. The subcritical crack growth parameters n and A were determined in a dynamic fatigue method at four decreasing loading rates from 110 MPa/s to 0.11 MPa/s in distilled water at 38 °C. For each loading rate Weibull statistics were performed and the Weibull moduli m and characteristic strengths σ0 were calculated. Using these data, strength-fracture probability-life time (SPT) predictions were derived for 1 day, 1 year, 5 years and 10 years, based on a static crack growth mechanism. Results: The "hipped" Y-TZP ceramic exhibited a higher initial strength (σc = 1618.18), characteristic strength (σ0 = 837.15) and fracture toughness (KIC = 4.52 MPa/m1/2) than the pre-sintered ceramic (σc = 1431, σ0 = 745.46 and KIC = 3.17 MPa/m1/2, respectively). Fatigue parameters, n and A, were 28.5 and 7.97 × 10-24 for Everest ZH and 30.15 and 5.47 × 10-20 for Everest ZS. The predicted fracture stress at 5% failure probability for a lifetime of 10 years was 259.34 MPa for Everest ZH and 263.2 MPa for Everest ZS. Conclusions: Although the "hipped" Y-TZP showed favorable initial mechanical properties, no significant difference could be found in the susceptibility of both ceramics to subcritical crack growth and their long-term strength. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dynamic fatigue; Lifetime analysis; SPT diagram; Subcritical crack growth; Zirconia ceramic